Imaging Surface Recombination Velocities of Grain Boundaries in Multicrystalline Silicon Wafers via Photoluminescence. Issue 1 (7th December 2016) - Sio, Hang Cheong; Phang, Sieu Pheng; Macdonald, Daniel
Abstract : We present a method for determining the effective surface recombination velocity ( S GB ) of grain boundaries in silicon wafers, based on the photoluminescence contrast of the grain boundary and numerical modeling of the luminescence signal. It is found that in single‐side passivated wafers, the luminescence contrast of a grain boundary is insensitive to lifetime variations in the neighboring grains, and hence can be directly correlated to S GB . In combination with pattern recognition methods to locate the grain boundaries, this allows the S GB of every grain boundary within a photoluminescence image to be explicitly determined and imaged. Abstract : A method for imaging the effective surface recombination velocity of grain boundaries in multicrystalline silicon wafers based on photoluminescence imaging is presented. The technique allows the overall recombination behaviors of grain boundaries in a multicrystalline wafer to be statistically quantified in absolute scale, which is important for studying grain boundaries and assessing their detrimental impact on the final solar cell performance.